2013
DOI: 10.1038/labinvest.2012.176
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of B-cell-activating factor signaling enhances hepatic steatosis induced by a high-fat diet and improves insulin sensitivity

Abstract: À mice fed a high-fat diet (HFD). Furthermore, the effect of BAFF on lipid metabolism in hepatocytes was analyzed in vitro. BAFF-R À / À mice showed improvements in HFD-induced obesity and insulin resistance. In addition, the number of B cells, levels of serum IgG, and inflammation of visceral fat were reduced in these mice. However, the expression of steatogenic genes and fatty acid deposition in the liver was higher in these mice than in control mice. BAFF was also found to downregulate the expression of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
1
40
1
Order By: Relevance
“…1D), which was partly consistent with a previous report that BAFF-R -/-mice were protected against HFD-induced obesity and insulin resistance [8]. BAFF -/-mice had improved glucose tolerance under HFD-fed condition, but, unlike BAFF-R -/-mice, were not protected against HFD-induced weight gain (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1D), which was partly consistent with a previous report that BAFF-R -/-mice were protected against HFD-induced obesity and insulin resistance [8]. BAFF -/-mice had improved glucose tolerance under HFD-fed condition, but, unlike BAFF-R -/-mice, were not protected against HFD-induced weight gain (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Kawasaki et al reported that BAFF-R knockout (BAFF-R -/-) mice were protected from high-fat diet-induced M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT adiposity and showed improved insulin sensitivity [8]. In their study, no difference of visceral fat weight between high-fat diet-fed BAFF-R -/-and wild type mice was observed but the inguinal fat weight was significantly lower in BAFF-R -/-mice.…”
Section: Introductionmentioning
confidence: 99%
“…B cell-activating factor (BAFF, TNFSF13B) is a cell survival and maturation factor for B cells, and overproduction of BAFF is associated with systemic autoimmune disease [91]. Recently, an increase of serum level of BAFF was identified in human NASH, and the serum BAFF level correlates with B-cell content in liver [92]. In addition, BAFF receptor-deficient mice display improved obesity and insulin resistance induced by HFD but also, unexpectedly, show enhanced hepatic steatosis, which indicates a protective role of BAFF in hepatic steatosis [92, 93].…”
Section: Inflammatory Mediators and Immune Alterationsmentioning
confidence: 99%
“…Recently, an increase of serum level of BAFF was identified in human NASH, and the serum BAFF level correlates with B-cell content in liver [92]. In addition, BAFF receptor-deficient mice display improved obesity and insulin resistance induced by HFD but also, unexpectedly, show enhanced hepatic steatosis, which indicates a protective role of BAFF in hepatic steatosis [92, 93]. However, contradictory observations on the B-cell's contribution to insulin resistance and NAFLD have also emerged.…”
Section: Inflammatory Mediators and Immune Alterationsmentioning
confidence: 99%
“…Several studies report that HF diets dysregulate B-cell driven humoral immunity ( 42,43 ). Winer et al ( 43 ) demonstrated that HF diets promote the accumulation of B cells in the adipose tissue that secrete pathogenic autoantibodies.…”
Section: Implications For the General Public And Clinical Trialsmentioning
confidence: 99%